Effect of LLDPE on impact, flexural and morphological properties PP/NR blend - Hassan, Azman (2002)
One of the most successful methods developed for modifying polymer properties is the rubber-toughening process by blending rubbers with plastics. Blends of polypropylene (PP) with elastomers are developed with the objective to overcome the inherent brittleness of PP at low temperatures and to enhance the impact strength at room temperature. In this study, a new impact-modified PP ternary blends based on PP/ natural rubber (NR)/linear low density polyethylene (LLDPE) is developed; the NR content ranged from 0 to 30%. The blends were prepared in a laboratory scale twin screw extruder. After mixing and pelletising, the samples were injection moulded and tested for mechanical properties. Impact, flexural and morphological properties of the blends were studied. An increase in impact strength but a decrease of flexural modulus was observed with increasing NR contents. The partial replacement of PP with LLDPE as the third component in PP/NR/LLDPE ternary blend had enhanced the impact strength with a slight decreased in flexural modulus. From morphologv features, LLDPE addition improves the dispersion or NR, affecting mainly the larger particles.